Polarized thinking and its relationship to cognitive dissonance among university students - علوان, طلال غالب (Sulaimani Journal for Humanities, 2019)
this study aims to detect the different levels of the dimensions of the dichotomous thinking and the cognitive dissonance . and also to detect the relationship of statistical significance between the averages dimensions of the dichotomous thinking and the cognitive dissonance, and to detect the differences of statistical significance between the averages of degrees of male and female in the dichotomous thinking and cognitive dissonance among students of the University of Sulaimani. This study was based on the descriptive method, on a sample of 300 university students divided equally into males and females, the study used the scale of the dichotomous thinking prepared by (Oshio, 2009) , and the scale of the cognitive dissonance prepared by (Chow, Cassel &Reiger, 2001) , Translation and rationing of the researcher , In order to achieve the objectives of the study and to answer its questions it based on appropriate statistical methods . in addition the study found that there are different levels in each of the dimensions of dichotomous thinking and cognitive dissonance, and there is a function relationship between the dichotomous thinking and its three dimensions (preference for dichotomy), (dichotomous beliefs), (profit and loss thinking), and cognitive dissonance. The study also detects the Existence of the differences between males and females in the degree of each of dichotomous thinking and cognitive dissonance. The study also presented a number of recommendations and suggestions.
Keywords: التفكير القطبي التنافر المعرفي طالب الجامعة جامعة السليمانية